2008
DOI: 10.1063/1.2963958
|View full text |Cite
|
Sign up to set email alerts
|

Wetting gradient induced separation of emulsions: A combined experimental and lattice Boltzmann computer simulation study

Abstract: Guided motion of emulsions is studied via combined experimental and theoretical investigations.The focus of the work is on basic issues related to driving forces generated via a step-wise (abrupt) change in wetting properties of the substrate along a given spatial direction. Experiments on binary emulsions unambiguously show that selective wettability of the one of the fluid components (water in our experiments) with respect to the two different parts of the substrate is sufficient in order to drive the separa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…It was found that the surface energy hysteresis is the key phenomenon to understand the different droplet coalescence dynamics on open surfaces and inside the gap. [25] Polymer Brushes with Immobilized NPs for Sensing Applications…”
Section: Ultrahydrophobic Brushes Wettability Gradients and Microflmentioning
confidence: 99%
“…It was found that the surface energy hysteresis is the key phenomenon to understand the different droplet coalescence dynamics on open surfaces and inside the gap. [25] Polymer Brushes with Immobilized NPs for Sensing Applications…”
Section: Ultrahydrophobic Brushes Wettability Gradients and Microflmentioning
confidence: 99%
“…Owing to the recent technological progress in the design and fabrication of micro-and nanotextured surfaces, physicaltexture-based solid surfaces have often been used as a tool to manipulate drops on the surfaces. A familiar example is the use of wettability-gradient surfaces [1][2][3], solid surfaces exhibiting a directional variation in surface wettability, in the transport of liquid drops on solid surfaces and separation of the components in an emulsion [4]. A drop placed gently on these surfaces gets propelled towards the higher-wettability region if it overcomes the resistive forces due to contact angle hysteresis and viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent separation of the immiscible phases may be performed by flow focusing, 26 manipulation of surface wetting characteristics, 16,17,24,27,28 or using capillary forces through a microporous hydrophobic membrane. 1,3,4 Another recent trend is to use hydrophobic ducts 29 through which an organic phase may be separated (somewhat similar to a hydrophobic membrane, but with larger pores and in fewer number), or to stabilize the interface of two contacting phases with the use of micropillars.…”
Section: Introductionmentioning
confidence: 99%